Development and validation of functional kompetitive allele-specific PCR markers for herbicide resistance in Brassica napus - Shi, Jianghua; Yu, Huasheng; Fu, Ying; Wang, Tanliu; Zhang, Yaofeng; Huang, Jixiang; Li, Sujuan; Zheng, Tao; Ni, Xiyuan; Zhao, Jianyi (Frontiers in Plant Science, 2023)
Effective weed control in the field is essential for maintaining favorable growing conditions and rapeseed yields. Sulfonylurea herbicides are one kind of most widely used herbicides worldwide, which control weeds by inhibiting acetolactate synthase (ALS). Molecular markers have been designed from polymorphic sites within the sequences of ALS genes, aiding marker-assisted selection in breeding herbicide-resistant rapeseed cultivars. However, most of them are not breeder friendly and have relatively limited application due to higher costs and lower throughput in the breeding projects. The aims of this study were to develop high throughput kompetitive allele-specific PCR (KASP) assays for herbicide resistance. We first cloned and sequenced BnALS1 and BnALS3 genes from susceptible cultivars and resistant 5N (als1als1/als3als3 double mutant). Sequence alignments of BnALS1 and BnALS3 genes for cultivars and 5N showed single nucleotide polymorphisms (SNPs) at positions 1676 and 1667 respectively. These two SNPs for BnALS1 and BnALS3 resulted in amino acid substitutions and were used to develop a KASP assay. These functional markers were validated in three distinct BC1F2 populations. The KASP assay developed in this study will be valuable for the high-throughput selection of elite materials with high herbicide resistance in rapeseed breeding programs.